EFFECT OF ELECTROMAGNETIC IRRADIATION AND ASPIRIN ON SURFACE TENSION OF HUMAN BLOOD PLASMA IN VITRO (Proceedings of the YSU B: Chemical and Biological Sciences, 2021)
In this work the effect of EMI EHF on change of the surface tension coefficient of human blood plasma under the effect of acetylsalicylic acid (ASA) as well as dependence of this parameter change on ASA effect duration and electromagnetic irradiation duration have been studied. It was shown that the plasma irradiation results in changing of the surface tension coefficient. At irradiation during 60 min the value of the given parameter increases, though, the further repeating irradiation does not induce an enhancement; some decrease is observed, but it remains higher, than the original value. It was also shown that ASA prevents development of relevant changes of blood plasma properties, particularly the value of the surface tension coefficient of plasma under the effect of EMI in millimeter range changes.
Keywords: human blood plasma; acetylsalicylic acid; electromagnetic irradiation; surface tension coefficient